(untitled) (Biological Sciences - PJSIR, 2002)
Preparati on, i solati on and characterizati on of some complexes deri ved rrom the i n teraction of G i rard D-ox i me wi th Cu(II), Zn(II), Cd(IT), Zr(IV), Co(TI) and Ni (TI) are descri bed. The ability of the stud ied meta l to coord i nate wi th the ligand i n enol or k eto forms was i n vest igated by pH t i trati on . Conductance measu remen ts and I R spectra of the sol i d com pl exes i n d i cate t hat d i acety l e m on oxi me Gira rd D coord i nates with Cu2+, Zn 2+ and Ni 2 + through C=O, C=N and N-OH grou ps as a triden tate l i gand bu t w i th CO2+ and Cd 2+ coord i nati on occurs throu gh C=N and N-OH grou ps as a bidentate l i gand. Format_i on constants oC these compl exes have been stud i ed potenti ometrical l y i n aqu eou s med i u m. The fonnati on constants i n crease as: Zr>Cd>Cu>Zn>Ni.